Nanomanufacturing of 2D Transition Metal Dichalcogenide Materials Using Self‐Assembled DNA Nanotubes. Issue 41 (27th August 2015) - Choi, Jungwook; Chen, Haorong; Li, Feiran; Yang, Lingming; Kim, Steve S.; Naik, Rajesh R.; Ye, Peide D.; Choi, Jong Hyun
Abstract : 2D transition metal dichalcogenides (TMDCs) are nanomanufactured using a generalized strategy with self‐assembled DNA nanotubes. DNA nanotubes of various lengths serve as lithographic etch masks for the dry etching of TMDCs. The nanostructured TMDCs are studied by atomic force microscopy, photoluminescence, and Raman spectroscopy. This parallel approach can be used to manufacture 2D TMDC nanostructures of arbitrary geometries with molecular‐scale precision.